Supply of Inputs and Procedures Non-Invasive and Micro-Invasive in Primary Care: Historical Series by Brazilian Regions - Manoelito Ferreira Silva-Junior; Larissa Yumi Ito; Letícia Simeoni Avais; Letícia Plocharski; Natália Almeida Bastos-Bitencourt; Ana Cláudia Rodrigues Chibinski; Alessandra de Souza Martins (Association of Support to Oral Health Research (APESB), 2024)
Objective: To analyze the supply of input and procedures, non-invasive and micro-invasive, for dental caries lesions in Primary Care in Brazil, comparing the Brazilian geographic regions in three different periods. Material and Methods: Historical series study based on secondary data extracted from the 1st Cycle (2012), 2nd (2014), and 3rd cycle (2018) of the External Evaluation of the National Program for Access and Quality of Primary Care. The proportions of Oral Health Teams offering non-invasive (fluor) and micro-invasive (sealants) supplies and procedures between Brazilian geographic regions were compared using the Chi-square test, using the Z Test adjusted by the Bonferroni method, and between the years (2012, 2014, and 2018) using the Cochran Q test (p<0.05). The percentage variation between the proportions per cycle was calculated. Results: The availability of inputs of fluor gel in Brazil increased between 2014 (91.6%) and 2018 (94.1%) (p<0.001), but statistically only in the Northeast and North (p<0.001). The offer of the topical fluorine procedure increased between 2012 (78.8%) and 2018 (87.4%) (p<0.001) in Brazil, with the most significant increase in the North (+7.5%) and Northeast (+22.0%). There was greater availability of inputs of sealants in Brazil between 2012 (56.8%) and 2018 (69.5%) (p<0.001) in Brazil, and more significant expansion in the Northeast (+43.4%). There was a greater offer of the sealing procedure in Brazil between 2014 (98.6%) and 2018 (98.5%), compared to 2012 (94.7%) (p<0.001), with more significant expansion in the North (+5.8%). Conclusion: There was an increase in the supply of input and procedures, non-invasive and micro-invasive, in Primary Care in Brazil. Despite maintaining regional inequalities, they were reduced, with greater expansion in the North and Northeast regions between the years evaluated.